Psychiatric comorbidities and concurrent substance use among people who inject drugs: a single-centre hospital-based study - Hadiya Kar; Abdul Majid Gania; Altaf Bandy; Nizam ud din Dar; Farhana Rafiq (Scientific Reports, 2023)
Abstract The management of people who inject drugs (PWID) is compounded by the presence of psychiatric comorbidities leading to frequent relapses and poor treatment outcomes. Early identification and treatment of psychiatric comorbidities should be included in the management to enhance treatment outcomes. The objective of this study was to estimate the prevalence of psychiatric comorbidities and concurrent substance use among opioid injectors. This hospital-based, cross-sectional study was conducted from March 2021 to August 2022. This study included opioid injectors of all ages and both sexes. The Mini International Neuropsychiatric Interview-7 (MINI-7) and WHO-ASSIST were used to determine psychiatric comorbidities and concurrent substance use, respectively. Both crude and adjusted odds ratios were calculated to assess associations among demographic variables, concurrent substance use and psychiatric comorbidities. Among the 328 opioid injectors, the overall prevalence of psychiatric comorbidities was 88.1%, with the majority (68.6%) having more than one comorbidity. The most common psychiatric comorbidities were panic disorder (41.2%), social anxiety disorder (40.5%), and antisocial personality disorder (39.3%). Concurrent use of alcoholic beverages doubled the risk of ASPD (odds ratio 2.14 (1.24–3.72)). Cocaine (odds ratio 2.36 (1.10–5.03)) and amphetamines (odds ratio 7.68 (2.21–26.65)) increased the risk of OCD. Daily heroin injections were negatively associated (odds ratio 0.18 (0.03–0.94)) with psychotic disorders. Younger age (adjusted odds ratio 0.20 (0.79–0.53)) and never married status (adjusted odds ratio 2.62 (1.06–6.47)) were the only significant variables in the regression analysis. In conclusion, opioid injectors had a higher prevalence of numerous psychiatric comorbidities. The most common comorbidity was anxiety disorders. Concurrent use of tobacco, cannabis, cocaine, inhalants, etc., greatly increased the risk of psychiatric comorbidities.